Insights into the Frequency and Distinguishing Features of Sleep Disorders in Pediatric Palliative Care Incorporating a Systematic Sleep Protocol - Larissa Alice Dreier; Boris Zernikow; Kathrin Stening; Julia Wager (MDPI AG, 2021)
Currently, no concrete figures on sleep disorders and sleep characteristics in children and adolescents with life-limiting conditions (LLC) and severe neurological impairment (SNI) based on pediatric palliative care professionals' assessment and following an official classification system such as the International Classification of Sleep Disorders (ICSD-3) exist. The ICSD-3 sleep disorders of inpatient children and adolescents with LLC and SNI (N = 70) were assessed by professionals using a recording sheet (two-year recruitment period). A systematic sleep protocol was applied to identify patients' sleep characteristics. Of these patients, 45.6% had sleep disorders, with the majority of them experiencing two different ones. Overall, the most frequently identified disorders were Chronic Insomnia and Circadian Sleep-Wake Disorder. Patients experiencing Chronic Insomnia showed more sleep phases during the daytime and more waking phases at nighttime than those unaffected. Patients with and without a Circadian Sleep-Wake Disorder additionally differed in the length of sleep phases during the daytime. Rapid changes between wakefulness and sleep were specifically characteristic of Hypersomnia. The study provides important insights into the prevalence and characteristics of individual ICSD-3 sleep disorders in pediatric palliative care. The findings may contribute to a targeted and efficient diagnosis and therapy of distressing sleep problems in seriously ill patients.